The Influence of Supervision and Discipline on Employee Performance Through Motivation at PT Bank Negara Indonesia (Persero) Tbk Jambi Branch Office - Maya Siska Simarmata; Pantun Bukit; Fakhrul Rozi Yamali (Green Publisher, 2026)
This study aims to describe supervision, discipline, work motivation, and employee performance, as well as to analyze the direct and indirect effects of supervision and discipline on work motivation and employee performance through work motivation at PT Bank Negara Indonesia (Persero) Tbk Jambi Branch Office. This research employed descriptive and verification methods with a quantitative approach. The population consisted of all employees of PT Bank Negara Indonesia (Persero) Tbk Jambi Branch Office, totaling 62 employees. The census method was used, whereby all population members were selected as respondents. Data were collected through questionnaires and analyzed using Path Analysis with the assistance of SPSS software. The results showed that supervision, discipline, work motivation, and employee performance were categorized as good. Partially, supervision had a positive and significant effect on work motivation with a path coefficient of 0.471, while discipline had a positive and significant effect on work motivation with a path coefficient of 0.481. Simultaneously, supervision and discipline significantly affected work motivation with an F-value of 188.431 and a significance value of 0.000. Supervision had a positive and significant effect on employee performance with a path coefficient of 0.600, while discipline had a positive and significant effect on employee performance with a path coefficient of 0.357. Simultaneously, supervision and discipline significantly affected employee performance with an F-value of 209.082 and a significance value of 0.000. Work motivation had a positive and significant effect on employee performance with a path coefficient of 0.919 and a t-value of 18.084. The findings also indicate that work motivation serves as an intervening variable that mediates the effects of supervision and discipline on employee performance. Therefore, improving supervision and discipline can enhance employee motivation, which in turn contributes to better employee performance at PT Bank Negara Indonesia (Persero) Tbk Jambi Branch Office.